Turn of the screw [videorecording (DVD)] - Bolt, Ben, 1952-; James, Henry, 1843-1916; May, Jodhi, 1975-; Ferris, Pam; Firth, Colin, 1960-; Sowerbutts, Joe, 1988-; Robinson, Grace (Masterpiece theatre (Television program), 2004)
Henry James' chilling ghost tale about a governess hired by a charming bachelor to look after two young children in a grand mansion in rural England where sinister events place their lives in jeopardy.